2010
DOI: 10.1212/wnl.0b013e3181dc1ae0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Report: The efficacy and safety of mitoxantrone (Novantrone) in the treatment of multiple sclerosis [RETIRED]

Abstract: Objective: The chemotherapeutic agent mitoxantrone was approved for use in multiple sclerosis (MS) in 2000. After a review of all the available evidence, the original report of the Therapeutics and Technology Assessment Subcommittee in 2003 concluded that mitoxantrone probably reduced clinical attack rates, MRI activity, and disease progression. Subsequent reports of decreased systolic function, heart failure, and leukemia prompted the US Food and Drug Administration to institute a "black box" warning in 2005.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(130 citation statements)
references
References 33 publications
6
117
2
5
Order By: Relevance
“…The majority of cases was APL and occurred within three years of mitoxantrone treatment. 101 The previous studies and reports collectively showed a high incidence of AML in multiple sclerosis and of AML-M3 after mitoxantrone exposure. Long and close follow up for hematologic changes in multiple sclerosis patients, particularly for those exposed to cytotoxic agents, should be part of their management.…”
Section: The Association Between Multiple Sclerosis and Myeloid Leukemiamentioning
confidence: 92%
“…The majority of cases was APL and occurred within three years of mitoxantrone treatment. 101 The previous studies and reports collectively showed a high incidence of AML in multiple sclerosis and of AML-M3 after mitoxantrone exposure. Long and close follow up for hematologic changes in multiple sclerosis patients, particularly for those exposed to cytotoxic agents, should be part of their management.…”
Section: The Association Between Multiple Sclerosis and Myeloid Leukemiamentioning
confidence: 92%
“…Mitoxantrone is approved for the treatment of worsening adult RRMS; however, given the risk of cardiotoxicity and high rates of leukemia [99], use of this therapy in pediatric MS is discouraged.…”
Section: Mitoxantronementioning
confidence: 99%
“…However, despite these therapeutic advances, a subset of patients seem refractory and rapidly develop severe neurological impairment, whereas other patients may have a slower progression of illness that ultimately results in marked functional disabilities. Only a single agent, mitoxantrone, has been shown to temporarily halt or slow the tempo of SP-MS [5,6], but even then, this occurs only in SP-MS patients who have highly active inflammatory events.HSCT was originally conceived as a method of rescuing patients from prolonged life-threatening bone marrow aplasia that results from the administration of high-dose total body irradiation or myeloablative chemotherapy. In the context of MS, a single administration of high-dose chemotherapy and total body irradiation (used individually or together) is meant to suppress or ablate the endogenous immune Electronic supplementary material The online version of this article…”
mentioning
confidence: 99%
“…However, despite these therapeutic advances, a subset of patients seem refractory and rapidly develop severe neurological impairment, whereas other patients may have a slower progression of illness that ultimately results in marked functional disabilities. Only a single agent, mitoxantrone, has been shown to temporarily halt or slow the tempo of SP-MS [5,6], but even then, this occurs only in SP-MS patients who have highly active inflammatory events.…”
mentioning
confidence: 99%